Design and Implementation of The Dude Mikrotik Server Using Telegram Bot as Monitoring Client Network and Internet Connection - Pratama, Ahmad Bagus Putra; Handoyo, Eko; Shodiq, Muhammad (Universitas Muhammadiyah Lamongan, 2025)
Network management and monitoring are crucial, especially in educational environments such as SMK Wachid Hasjim Maduran, which has a network with various devices and connected clients. The high number of users accessing the network often leads to bandwidth issues. This research aims to implement The Dude, a MikroTik-based network monitoring application, to detect and address bandwidth problems and monitor the status of client devices (up/down). The system is equipped with a notification feature that sends real-time information to network administrators via Telegram regarding the network's condition. Monitoring is conducted using The Dude, which can map all devices in the network and monitor their performance and status. When a bandwidth issue occurs or a client device goes down, the system automatically sends a notification to Telegram. This allows administrators to take the necessary actions promptly without always being in front of the computer. The results of this implementation show that utilizing The Dude in combination with Telegram notifications is effective in real-time network monitoring, reducing downtime, and improving response to network issues. This system is expected to be an efficient solution for network management in educational environments and can be adopted by other institutions facing similar challenges. Keywords - MikroTik, Monitoring, Telegram Notification, The Dude.